Seguros agrícolas paramétricos: Una revisión de la literatura - Luis Carlos Jemio (Institute for Advanced Development Studies (INESAD), 2024)
– Agricultural insurances based on a climate index are an innovative form of insurance that represent a viable alternative for low-income countries. Such insurances are tied to a climatic index (e.g. the level of precipitation, temperature, humidity or crop yield) rather than an actual loss. This characteristic makes it possible to solve some problems related to traditional agricultural insurances, such as high administrative costs, moral hazard and adverse selection. However, insurances based on a climate index face challenges for their implementation, such as the lack of reliable and accurate information, base risk problems and complexity in their design and implementation. In this document I analyze the conceptual and methodological factors that must be considered to develop an agricultural index based on a climate index for quinoa producers in Bolivia. For this purpose, in addition to analyzing conceptual factors, I study practical cases developed both internationally and in Bolivia.
Keywords: D89; G22; Q01; Q14; 330; Agricultural insurance; parametric insurance; quinoa; Bolivia; risk mitigation